Estimating the neutron background toward the measurement of neutrino mixing angle [theta][subscript]1[subscript]3 with the Double Chooz detector - Shrestha, Deepak (Kansas State University, 2013)
Double Chooz is a reactor neutrino experiment which has shown evidence of electron anti-neutrino disappearance at 1 km distance. It has been able to exclude the no-oscillation hypothesis at 99.8% CL (2.9ς) with only one detector. From a rate plus spectral shape analysis, the value of sin²2θ₁₃ was found to be 0.109±0.030(stat) ± 0.025(syst). Correlated events mimicking an anti-neutrino event are one of the most important backgrounds for a reactor neutrino experiment like Double Chooz which measured the neutrino mixing angle θ₁₃. Cosmic muons passing through the rock surrounding the detector produce fast neutrons which give rise to correlated events through proton recoil followed by a neutron capture. Muons stopping around the chimney region subsequently decay into Michel electrons also contributing to the correlated background. Measurement of the shape and rate of this background is very important for the precise measurement of θ₁₃. Experimental techniques to estimate of the shape and rate of this background in the Double Chooz far detector are presented in this thesis.
Keywords: Neutron Background; Double Chooz; Particle Physics (0798); Physics (0605)